Environmental policies, waste and circular convergence in the European context - Emy Zecca; Andrea Pronti; Elisa Chioatto (Insights into Regional Development)
This work explores the transition process towards a circular economic model in the European context. By placing the role of policies and waste as a focus of the debate, it first examines the possible effects that a stringent policy can generate and, secondly, how much waste and its management can influence the goodness of the transition process. By analyzing European data on major indicators of circularity, waste generation, and management, this paper attempts to provide a snapshot of the European situation and its different speeds along the transition path. In light of the recent development programs established by European institutions in the aftermath of the Covid-19 pandemic that strained the world economy, the trends show how program resources should be directed towards key sustainability sectors that can stimulate European countries towards a common circular pathway.